Use of autologous bone graft with bioactive glass as a bone substitute in the treatment of large-sized bone defects of the femur and tibia - Findeisen, Sebastian; Gräfe, Niklas; Schwilk, Melanie; Ferbert, Thomas; Helbig, Lars; Haubruck, Patrick; Schmidmaier, Gerhard; Tanner, Michael Christopher (Journal of Personalized Medicine, 2023)
Background: Managing bone defects in non-union surgery remains challenging, especially in cases of large defects exceeding 5 cm in size. Historically, amputation and compound osteosynthesis with a remaining PMMA spacer have been viable and commonly used options. The risk of non-union after fractures varies between 2% and 30% and is dependent on various factors. Autologous bone grafts from the iliac crest are still considered the gold standard but are limited in availability, prompting consideration of artificial grafts. Objectives: The aims and objectives of the study are as follows: 1. To evaluate the radiological outcome of e.g., the consolidation and thus the stability of the bone (three out of four consolidated cortices/Lane-Sandhu-score of at least 3) by using S53P4-type bioactive glass (BaG) as a substitute material for large-sized bone defects in combination with autologous bone using the RIA technique. 2. To determine noticeable data-points as a base for future studies. Methods: In our clinic, 13 patients received bioactive glass (BaG) as a substitute in non-union therapy to promote osteoconductive aspects. BaG is a synthetic material composed of sodium, silicate, calcium, and phosphate. The primary endpoint of our study was to evaluate the radiological consolidation of bone after one and two years. To assess bone stabilization, we used a modified Lane-Sandhu score, considering only radiological criteria. A bone was considered stabilized if it achieved a minimum score of 3. For full consolidation (all four cortices consolidated), a minimum score of 4 was required. Each bone defect exceeded 5 cm in length, with an average size of 6.69 ± 1.92 cm. Results: The mean follow-up period for patients without final bone consolidation was 34.25 months, with a standard deviation of 14.57 months, a median of 32.00 months and a range of 33 months. In contrast, patients with a fully consolidated non-union had an average follow-up of 20.11 ± 15.69 months and a range of 45 months. Overall, the mean time from non-union surgery to consolidation for patients who achieved final union was 14.91 ± 6.70 months. After one year, six patients (46.2%) achieved complete bone consolidation according to the Lane-Sandhu score. Three patients (23.1%) displayed evident callus formation with expected stability, while three patients (23.1%) did not develop any callus, and one patient only formed a minimal callus with no expected stability. After two years, 9 out of 13 patients (69.2%) had a score of 4. The remaining four patients (30.8%) without expected stability either did not heal within two years or required a revision during that time. Conclusions: Bioactive glass (BaG) in combination with autologous bone (RIA) appears to be a suitable filler material for treating extensive non-unions of the femur and tibia. This approach seems to show non-inferiority to treatment with Tricalcium Phosphate (TCP). To ensure the success of this treatment, it is crucial to validate the procedure through a randomized controlled trial (RCT) with a control group using TCP, which would provide higher statistical power and more reliable results.